Management and survival of patients with leptomeningeal disease from breast cancer: a case series. (February 2017) - Feng, Sophie; Roberts, Kate; Ghimire, Ram; Sanmugarajah, Jasotha
Leptomeningeal disease (LMD) in breast cancer is a rare complication and often portends a poor prognosis. There is a lack of randomized data guiding treatment decisions and no accepted standard of care in the management of LMD. We retrospectively analyzed the treatment and outcomes of six patients diagnosed with LMD at our institution. All patients were treated with intrathecal methotrexate, resulting in a median overall survival after LMD diagnosis of 18.5 weeks, with two patients surviving over 30 weeks. An Ommaya reservoir was used to deliver chemotherapy and this was well tolerated with minimal toxicity. The use of intrathecal methotrexate is a safe option, however, further studies are required to define its role in the management of LMD and identify populations that may derive a benefit.